Stakeholder Response to Information on Social Responsibility and Income Smoothing - Ardhya Yudistira Adi Nanggala (INDONESIAN JOURNAL OF ACCOUNTING AND GOVERNANCE, 2023)
This study aims to examine the response of stakeholder and shareholder to the information submitted by the company. In the discussion of signaling theory, information is a signal and is expected to be responded to by shareholder and stakeholder. The research population is manufacturing companies from 2018 to 2021 in Indonesia, with a purposive sample of 64 companies-years of observation. There are five hypotheses tested using partial least squares. Three hypotheses were successfully accepted and rejected the others. The test results prove that stakeholder respond to CSR as a positive signal for the company but fail to demonstrate the role of income smoothing. Different things are shown that income smoothing is a signal that is responded to by shareholder but is not responded to by stakeholder. The firm value becomes the guideline for the value that stakeholder provides to the company. Testing the mediating role shows that firm value is not an intervening variable because it does not have a direct relationship with growth. Income smoothing affects firm value, and then firm value affects growth. In the development of science, these findings can be used to develop accounting theory. Evidence of stakeholder reactions to signals given by shareholder and management can lead to a process of generalizing and falsifying theories to strengthen financial accounting theory.